2019
DOI: 10.1163/22941932-40190219
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mistletoe (Viscum album) on branch wood and needle anatomy of Scots pine (Pinus sylvestris)

Abstract: Mistletoes are hemi-parasitic plants growing on many tree species. They grow on the tree branches or trunk of a tree and form root-like structures called haustoria that penetrate into the tree, taking up water and mineral nutrients. Mistletoe is capable of causing a variety of effects to its hosts, including changes in wood formation and leaf development. We investigate and discuss the effects of pine mistletoe (Viscum album ssp. austriacum, Santalaceae) on branch wood and needle anatomy of Scots pine (Pinus s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
0
9
0
1
Order By: Relevance
“…Mistletoes contribute to increased transpiration, especially in years of water deficit, and cause marked weakening of infested trees [39,40]. According to Ozturk et al [41] mistletoe influences the anatomy of wood and needles, leading to partial or total death of the host during periods of drought [42,43], which is why it is important forest parasite. The high mortality in Scots pine stands in some places across Europe has been reported to be at least partly attributable to mistletoe infestation [24,44].…”
Section: Introductionmentioning
confidence: 99%
“…Mistletoes contribute to increased transpiration, especially in years of water deficit, and cause marked weakening of infested trees [39,40]. According to Ozturk et al [41] mistletoe influences the anatomy of wood and needles, leading to partial or total death of the host during periods of drought [42,43], which is why it is important forest parasite. The high mortality in Scots pine stands in some places across Europe has been reported to be at least partly attributable to mistletoe infestation [24,44].…”
Section: Introductionmentioning
confidence: 99%
“…), and the European mistletoes ( Viscum spp.) [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ]. Mistletoes are characterized as hemiparasitic plants because of their reduced photosynthetic efficiency and the absence of a true rooting feature [ 18 , 64 ].…”
Section: The Biology Of Mistletoementioning
confidence: 99%
“…Pine mistletoe infection influences the anatomical (Ozturk et al, 2019) and morphological (Barbu, 2012;Rigling et al, 2010) characteristics of needles. The results indicated that mean needle length, width and needle area decreased significantly (p<0.05) as a result of mistletoe infection (Table 2).…”
Section: Effects Of Mistletoe On Needle Characteristicsmentioning
confidence: 99%
“…Previous studies have clearly shown the effects of mistletoe on tree growth (Bilgili et al, 2020;Kanat et al, 2010), wood anatomy (Gol et al, 2018;Ozturk et al, 2019), biology (Mutlu et al, 2016b;Persoh et al, 2010), physiology (Ehleringer et al, 1986;Glatzel & Geils, 2009;Mutlu et al, 2016a) and morphology (Rigling et al, 2010) of host plants. In addition, the relationship between leaf area and sapwood area have been examined and documented in many broadleaved (Meadows & Hodges, 2002) and conifer species (Bancalari et al, 1987;Waring et al, 1982) including Scots pine (Albrektson, 1984;Berninger & Nikinmaa, 1994;Whitehead, 1978).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation